2001
DOI: 10.1097/00003226-200111000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of MUC5AC Protein in Human Tears

Abstract: A method was established to quantify MUC5AC in human tear samples obtained on Schirmer strips. There was no correlation between the amount of MUC5AC and age or gender in the healthy population. Dry eye disease patients, however, typically showed reduced concentrations of soluble MUC5AC in the tear film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 10 publications
2
56
2
Order By: Relevance
“…Previous reports that MUCs 1, 4 and 5AC are present in human tear fluid (Ellingham et al, 1997;Garcher et al, 1998;Jumblatt et al, 1999;Pflugfelder et al, 2000;Zhao et al, 2001;Argueso et al, 2002) have been corroborated by this study. This report also corroborates the presence of low levels of MUC2 in tears (McKenzie et al, 2000), with weak binding of 2 of the 3 antibodies tested on 100μg of total tear protein, an amount 10 times greater than the mid-linear range for MUC5AC detection.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Previous reports that MUCs 1, 4 and 5AC are present in human tear fluid (Ellingham et al, 1997;Garcher et al, 1998;Jumblatt et al, 1999;Pflugfelder et al, 2000;Zhao et al, 2001;Argueso et al, 2002) have been corroborated by this study. This report also corroborates the presence of low levels of MUC2 in tears (McKenzie et al, 2000), with weak binding of 2 of the 3 antibodies tested on 100μg of total tear protein, an amount 10 times greater than the mid-linear range for MUC5AC detection.…”
Section: Discussionsupporting
confidence: 87%
“…The quantitative assay for mucins in tears reported in this study has several advantages over previously reported ELISA and Schirmer strip collection assays (Garcher et al, 1998;Zhao et al, 2001;Argueso et al, 2002). Garcher et al (Garcher et al, 1998) assayed tears eluted from impression cytology samples using an ELISA for the tumor marker CA19-9, which has since been identified as a marker for MUC1/Y (Akagi et al, 2001), a splice variant of MUC1 that is missing the tandem repeat domain (Zrihan-Licht et al, 1994).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations